The effect of industrialization on birth seasonality in Iceland. An Empirical Analysis - Davíð Freyr Björnsson 1992- (2016)
The seasonality of births is a phenomenon that is widely observed. A number of variables have been found to be correlated with birth seasonality although a consistent explanation has not yet been found (Lam and Miron, 1991). Length of the photoperiod and temperature (Manfredini, 2009) have been proposed as explanations as well as rainfall (Pitt and Siegel, 2009) and agricultural cycles (Ellison et al. 2005, Pitt and Siegel 2009, Bailey et al. 1992). Iceland was a highly agricultural society in the 19th century but experienced a late and rapid industrialization in a matter of decades at the beginning of the 20th century. The industrialization became the driver of urbanization. Alongside the industrialization was a dramatic change in the magnitude and pattern of the seasonality of births. Ellison et. al (2005) causally links the seasonal variation in workload and food availability in subsistence agricultural societies to birth seasonality. The economy’s emphasis on agriculture diminished greatly and much more rapidly than in other European countries (Jonsson, 2004). Therefore the effect of agriculture on the seasonal pattern of births should be easier to detect. In this thesis the seasonal patterns of birth in Iceland from the second half of the 19th century well into the 21st are examined. Using principal component analysis the findings of this study show that the transition from agriculture to the fisheries at the beginning of the 20th century had a significant effect on the seasonal pattern of births.